RANCANG BANGUN ALAT PENGERING SISTEM ISOLATOR BERLAPIS PAPAN BATU KERIKIL SEBAGAI PENYIMPAN PANAS - Juandi M; Ismawan Ismawan; Usman Malik (Komunikasi Fisika Indonesia, 2018)
Research on the design of a dryer with an insylation system made of pebble and board for heat storage. This research as conducted using experimental method by making a dryer using biomass energy sources . The objectives of the study were to measurins the heat rate lost from each side of the dryer, the heat energy generated from the combustion of the coconut shell  the moisture content of drying wet clothing, the efficiency of the drying time The results showed the design of a dryer with an insylation system made of pebble and board for heat storage works well. The temperature inside the room is ranges from (40-68°C). The total rate of heat energy lost in the 10th minute is 6,527.54 J/s and continued to decrease to 60th minute by 3263.77 J/s. The heat energy rate resulting from the combustion of coconut shells at 10th mins is 10520 J/s and continued to decrease to 60th minute by 1753.33 J/s. Reduced moisture content of wet clothes reached 2.439% at 60 minutes. Efficiency of drying time reaches 85.7%. The efficiency of the average biomass energy source is 90%.